Dinamika Gender Dalam Pertanian : Menganalisis Kontribusi Perempuan Dalam Pembangunan Perekonomian Perspektif Hukum Islam - Ardah, Lukman; Mubarak, Kasyful; Mubarak, Husni; K, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the role of women in the agricultural sector, which often receives insufficient attention despite their significant contributions to food security and economic development. The research aims to analyze women's contributions in this sector from the perspective of Islamic law, highlighting the social, cultural, and structural challenges they face. The research employs a literature review methodology, encompassing the analysis of various academic sources, Islamic legal documents, and relevant empirical studies. The findings indicate that women play a vital role in every stage of agricultural processes, from production to the distribution of crops. However, barriers such as limited access to land, capital, technology, and education often impede their full potential. Islamic law upholds the principles of gender justice and equality, affirming women's rights to actively participate in economic activities, including agriculture. The study underscores the importance of empowering women through policies that enhance resource access, education, and legal protection while addressing patriarchal norms that restrict their role in decision-making.